MODELLING OF LAND SUBSIDENCE ALONG TANAH MAS -PELABUHAN SECTION SEMARANG CITY USING FINITE ELEMENT METHOD - Dwi Sarah; Arifan J. Syahbana; R. Fajar Lubis; Asep Mulyono (JURNAL RISET GEOLOGI DAN PERTAMBANGAN, 2011)
ABSTRACT Land subsidence has been an apparent problem in the northern part of Semarang city, Central Java, which has caused enormous physical and economical impacts. This area is underlain by alluvium sediments of clay, silt, sand and gravel. The nature of the alluvium soil is soft and highly compressible which induces natural consolidation to occur. The lowering of groundwater table due to exploitation and loads of building and earth fill accelerate the rate of consolidation settlement. A study of land subsidence modeling was carried out in the northern part of Semarang city. Collection and analysis of data on the geology, hydrology, soil properties and monitored settlements were conducted. Modeling of land subsidence involved stress deformation analysis using finite element method. The settlements computed for selected section of the city of Semarang were compared with measurements of settlement in the city area. The simulation results appear to be in reasonably good agreement with the measurement results. Simulation results at selected section indicated that the contribution of lowering groundwater table factor accounts for less than 50% of total monitored subsidence. Meanwhile simulation results using application of external loading and lowering of groundwater table showed better agreement with the monitored subsidence. Information of magnitude and factors causing land subsidence is important particularly for city planning purposes.